Branch Rickey : a biography - Polner, Murray. 4 0 16; 5 (New York : Atheneum, 1982)
Presents the life story of the man who broke baseball's color bar by hiring Jackie Robinson for the Brooklyn Dodgers.
Includes index.
Bibliography: p. 289-293.
School Library Journal
Young Adult;Young Adult
Keywords: 2 -- Rickey, Branch, -- 0 -- 1881-1965.; 6; History. -- Executives;Baseball -- United States;United States -- 20 -- Biography; 20; 2